Aggressive Nodular Malignant Melanoma - Myers, Daniel J (Cureus, 2021)
A subtype of malignant melanomas, nodular melanoma often carries a poor prognosis because of local invasion and frequent distant metastasis. Here, we report a case of progressive dyspnea due to one of the largest primary melanomas in the literature to date along with management strategies and elucidate some of the reasons why patients delay seeking care.